EFEKTIFITAS MEJA TPS DALAM MENINGKATKAN PEMAHAMAN OPERASI PENJUMLAHAN, PENGURANGAN DAN PERKALIAN BILANGAN ASLI UNTUK SISWA SD KELAS 2 DAN 3 - Magdalia Frisca Madelyn Sitanggang; Hary Nugraha; Ade Suci Ramadhani; Rifda Ulfa Mukhtar (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2019)
The learning activities in the Quantum Education is having problems in learning activities arithmetic operation of calculating natural numbers, this due to mathematics is abstract. So it's very difficult to be understood by students with age range of 7-11 years. Teaching media is learning facilities that can concretize abstract teaching materials. The purpose of this activity is to see the success of TPS Desk as medium of mathematics learning that can improve students' understanding learning material of operations for natural numbers. The method used activity is the design, use and mentoring business bookkeeping. The results of the activities that have been done show that TPS Desk managed to increase students' understanding in learning activities arithmetic operations on natural numbers.